Risk Factors for Pneumonia in Children under 5 Years in a Teaching Hospital in Nepal - Karki, S; Fitzpatrick, AL; Shrestha, S (Kathmandu University Medical Journal, 2015)
Background Pneumonia is a leading cause of mortality among children under-five years of age globally. The WHO (2014) has reported that indoor air pollution caused by cooking and heating with biomass fuel, living in crowed homes and parenting smoking are risk factors of pneumonia.Objectives The objective of the study was to identify the risk factors for pneumonia among children under-5 years of age.Methods A case control study was carried out among the mothers having under-5 years children who were admitted in the paediatric ward of Dhulikhel Hospital in 2012/13. A convenience sampling technique was used to select 50 children with pneumonia and 150 children with non-pneumonia diseases matched on age, sex and setting. A semi-structured interview consisting of questions related to risk factors for pneumonia was used to collect data from mothers of both cases and controls.Results Sex of the child did not differ by case/control group whereas the children with pneumonia were slightly older with 26% cases and 15% controls older than 3 years of age. Mother’s education was similar in both groups as was family income. Living in a household with a chulo with smoke increased the odds of having pneumonia significantly, with the risk almost 4 times greater if the chulo was located within the same building (OR: 3.76, 95% CI: 1.20-11.82, p=0.02). Children who had diarrhea in the past 3 months were protected from pneumonia (OR: 0.38, 95% CI: 0.18- 0.82, p=0.01). An increasing trend of pneumonia was observed among children of tobacco smoking parents with greater risk if both parents smoked; it was, however, not statically significant (OR: 2.21, 95% CI: 0.56-8.82, p=0.26).Conclusion The present study suggests that two factors related to smoke, presence of a smoky chulo in a household and both parents smoking, are modifiable risk factors related to pneumonia in young children. Reliable longitudinal studies, interventions, and programs to educate parents in prevention are important for reducing mortality and morbidities related to acute respiratory illnesses in Nepal.Kathmandu University Medical Journal Vol.12(4) 2014; 247-252